The Pragmatic Import of Humorous Utterances in Kiswahili Buying and Selling Encounters (Mwanga wa Lugha, 2019)
This paper analyses humour as a pragmatic resource that interactants draw on to promote interpersonal relations between themselves as they engage each other in the negotiation exercise. Humour is discussed as a pragmatic and strategic resource that the interactants tap in order to amicably transact, besides enhancing their solidarity and mutual understanding. They therefore position themselves as equals in the market encounter. Humour is one of the essential tools for exploring the ways in which market conversation achieves serious social effects, while appearing to be no more than ways of having a few laughs together. The author discusses humour in the context of the market negotiation where, the two parties engage each other in a relaxed talk. As such, the two parties interact as “free and equal individuals who are willing to construct a context in which they are free to engage each other in the transaction encounter in the way and manner that pleases them.